Comparação de testes laboratoriais para detecção de Vírus Respiratório Sincicial Humano (VRSH) em amostras clínicas de crianças ambulatoriais e adultos transplantados de medula óssea com suspeita de infecção respiratória aguda atendidos no Hospital São Paulo - Moreira, Luciana Peniche [UNIFESP] (2011)
The human respiratory syncytial virus (HRSV) is considered the main cause of lower respiratory tract infection, mainly bronchiolitis and pneumonia in children and newborn, and has been an important cause of acute respiratory infection in immunocompromised patients. There is much diversity of available techniques for diagnosis of HRSV differing in sensitivity, cost and time to obtain results. Pre-analytical factors such as samples collection and processing, may affect results. This study had analyzed some available methods for HRSV diagnosis and verified if the laboratory services offered to the Sao Paulo Hospital (HSP) are satisfactory in the identification of infected patients. We analyzed two patients groups with respiratory tract infection symptoms in the year 2008, the first one included community children under 12 years old, attended at “Núcleo de Assistência a Saúde do Funcionário (NASF)”, and the second one included patients on transplant program, attended on the bone marrow transplant (BMT) unit of HSP. Children samples were tested by viral isolation (ISO), direct immunofluorescence (DIF) and polymerase chain reaction preceded by reverse transcription (RT-PCR), the immunocompromised patients samples were also tested in a immunochromatographic assay (IT). The comparisons among the techniques were performed using the RT-PCR as gold standard. The detection peak of HRSV in children occurred in April, and in the BMT group the virus was detected evenly between the months of March and June. Of the 128 children samples, 18 (14%) were positive for HRSV in at least one technique. The positivity for ISO, DIF, and RT-PCR was 3.1%, 11.7% and 14% respectively. The kappa coefficient from comparisons between RT-PCR and ISO was 0.32 and 0.89, from RT-PCR and DIF. Among the 111 samples of immunocompromised patients, 19 (17.1%) were positive for HRSV in at least one technique. The positivity for ISO, IT, DIF and RTPCR was 0.96%, 4%, 10.8% and 12.6% respectively. The kappa coefficient from comparison between RT-PCR and ISO was 0.13, 0.48 from RT-PCR and DIF and 0.46 from RT-PCR and IT comparisons. We conclude that the low sensitivity of both viral isolation and immunocromatographic assay do not support its use on routine practice. For the children group, DIF is considered sufficient for epidemiological surveillance. For immunocompromised patients, the DIF should be used for surveillance, but, in some special circumstances, RT-PCR should be considered as an important tool to increase the detection rates of HRSV.